Tenascin-C in primary Merkel cell carcinoma. Issue 3 (25th February 2005) - Koljonen, V; Jahkola, T; Tukiainen, E; Granroth, G; Haglund, C; Böhling, T
Abstract : Background/Aims: Merkel cell carcinoma (MCC) is a rare malignant cutaneous neuroendocrine tumour that mostly affects the elderly. It shows rapid progression of the primary tumour, together with a vertical growth pattern into the underlying subcutaneous tissue. Metastatic dissemination to regional lymph nodes is early and frequent. Tenascin-C (Tn-C) is a large extracellular matrix glycoprotein that is expressed in various benign and malignant processes. Expression of Tn-C is also associated with invasion and cellular proliferation, and is often downregulated in fully evolved advanced carcinomas. In previous studies, Tn-C expression correlated with prognosis in tumours of different origin. Methods: Immunohistochemistry was used to investigate the expression of Tn-C in 25 MCC specimens and to evaluate the prognostic importance of this glycoprotein. Results: Seventeen samples expressed Tn-C. Staining was mainly seen in the invasion borders and within the connective tissue septae inside the tumours. The expression of Tn-C correlated significantly with large tumour size. There was also frequent expression of Tn-C in primary tumours with metastatic dissemination. Most of the Tn-C negative samples were of small size. Conclusions: Tn-C expression seems to increase with tumour size and malignant behaviour. Expression was slightly enhanced in tumours with high proliferative indices. Expression is seen mainly in areas of invasive growth and, in this respect, resembles that of other invasive tumours.